Creating a Market Pull for Cleaner Production - Shah, Jigar (World Bank, Washington, DC, 2012)
Of the many challenges to scaling up the Cleaner Production (CP) advisory services program, the most difficult one relates to the market: engaging clients and building a robust pipeline of projects. In this article, the author concentrate mainly on the lessons learned from International Finance Corporation (IFC) regions on approaches to selling CP in a highly replicable manner. Such lessons will greatly help us reduce transaction costs and time for providing CP advisory services.